2018
DOI: 10.3390/met8090677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooling Path on Microstructure Features and Tensile Properties in a Low Carbon Mo-V-Ti-N Steel

Abstract: The two-stage controlled rolling and cooling of a low carbon Mo-V-Ti-N steel at different cooling paths was simulated through a Gleeble 3500 system. The microstructure and tensile properties of each sample were examined by estimating their dependence on the cooling paths. It was indicated that a mixed microstructure of polygonal ferrite (PF), acicular ferrite (AF), granular bainitic ferrite (GBF), and a martensite-austenite (M-A) constituent was developed in each sample. Results showed that application of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(81 reference statements)
1
1
0
Order By: Relevance
“…[ 15,32,33 ] A notable increase of the dislocation density was also observed in the specimens isothermally transformed at the 590 °C temperature compared to the other CTs. These values were comparable with the low carbon Mo–V–Ti–N steels with a mixed microstructure of polygonal ferrite, acicular ferrite, granular bainitic ferrite, and a martensite–austenite constituent, [ 53 ] although the present steels were fully ferritic, as shown in Figure 1. Thus, the present results demonstrated that a significant difference between the dislocation densities can be achieved in the low‐carbon low‐alloyed steels by changing the CT.…”
Section: Resultssupporting
confidence: 83%
“…[ 15,32,33 ] A notable increase of the dislocation density was also observed in the specimens isothermally transformed at the 590 °C temperature compared to the other CTs. These values were comparable with the low carbon Mo–V–Ti–N steels with a mixed microstructure of polygonal ferrite, acicular ferrite, granular bainitic ferrite, and a martensite–austenite constituent, [ 53 ] although the present steels were fully ferritic, as shown in Figure 1. Thus, the present results demonstrated that a significant difference between the dislocation densities can be achieved in the low‐carbon low‐alloyed steels by changing the CT.…”
Section: Resultssupporting
confidence: 83%
“…Table 3 shows that the average dislocation density in the QF+GBF matrix of steels decreases with an increase in Si content, owing to the increased transformation temperature of QF+GBF. The contribution of dislocation enhancement (σ ρ ) to the YS can be estimated from the following equation [31,33,34]:…”
Section: Effect Of Si Content On the Tensile Propertiesmentioning
confidence: 99%
“…The contribution of precipitation strengthening (σ p ) to the YS can be estimated using Equation (6) [34][35][36][37], which is based on the fraction and average size of precipitates:…”
Section: Effect Of Si Content On the Tensile Propertiesmentioning
confidence: 99%
“…Application of TMCP leads to the decrease of the effective ferrite grain size and the increases of the dispersed precipitate and the dislocation density, which eventually resulted in the improvement of comprehensive properties such as strength, toughness and weldability. It also improves the morphology of MA (martensite-austenite) constituent, which lowered the yield ratio and, thereby, enhanced the capacity for strain hardening [15]. Microalloying elements can effectively control the microstructure of steel and improve its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%